2019
DOI: 10.1007/s00268-019-05040-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection: Its Impact on Patients with Appendicitis in Botswana

Abstract: Background To compare the presentation, management, and outcome of HIV-positive patients with appendicitis to those of HIV-negative patients with appendicitis. Summary Background Data: The literature is limited regarding the impact of HIV infection on patients with appendicitis. Methods A retrospective review of patients with appendicitis and known HIV status admitted to Princess Marina Hospital, Gaborone, Botswana, aged 13 years and greater was performed from January 2013 to December 2015. Data on patient dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 26 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…10,11 The role of immune status and CD4 count is also linked with AA. For example, Bedada et al 11 showed that high postoperative complications and mortality in HIV patients with AA can be associated with a CD4 count <200. León-Ballesteros et al…”
Section: Hiv and Appendicitismentioning
confidence: 99%
See 4 more Smart Citations
“…10,11 The role of immune status and CD4 count is also linked with AA. For example, Bedada et al 11 showed that high postoperative complications and mortality in HIV patients with AA can be associated with a CD4 count <200. León-Ballesteros et al…”
Section: Hiv and Appendicitismentioning
confidence: 99%
“…This syndrome is associated with initiation of combined antiretroviral therapy (cART), which initiates a pathological inflammatory response to a previous infection resulting in appendicitis. 10,11 Different mechanisms were also suggested to have role in the AA such as strong interferon response in the appendix may in part endorse a viral aetiology for the inflammation. Such observation can be also endorsed by the fact that the appendix is also part of the gut lymphoid tissues and this may further explain the involvement of the mucosal B and T cells and the replication of the HIV virus in the appendix.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations